WTO Dispute Settlement System : The Appellate Body Crisis - Rücklová, Alžběta; Štěrbová, Ludmila, 1957-; Šustrová, Lenka; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
In the past twenty-five years the World Trade Organization has become one of the most prominent and successful international organizations. It owes a significant part of its success to its dispute settlement system, which was succeeded the previous system under the GATT 1947. However, the system is now in danger. Its Appellate Body has become unable to hear any new appeals, which puts at risk the whole dispute settlement system. This thesis studies theses of students from the University of Economics, Prague, who have analysed various WTO disputes, from 2008 to 2019. It examines their findings in order to establish whether dispute settlement has positively or negatively impacted international trade. It also analyses the current Appellate Body crisis, which has unravelled during the previous year, looking into the reasons that have led to the crisis and what steps have been taken to solve it. The crisis is still ongoing, multiple members’ proposals have surfaced, and a group of members have established interim appeal arbitration. But there are no signs of a solution any time soon. Meanwhile, the future of the WTO remains at stake.
Vedoucí práce: Ludmila Štěrbová
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: mezinárodní obchod [obor dipl. práce]; diplomové práce; master's theses